IMPLEMENTASI MEDIA FLASHCARD PADA PEMBELAJARAN TEMATIK DI MADRASAH IBTIDAIYAH - Isni Susanti; fitria Martanti; Ummu Jauharin Farda (Universitas Wahid Hasyim Semarang, 2021)
AbstractThe goal of this study was to determine student learning outcomes in thematic learning using Flashcard Media in sub-theme 2 forms of learning objects at Class III Madrasah Ibtidaiyah Annur Pedurungan Semarang. This study was carried out using Classroom Action Research (CAR). Data was gathered through the use of evaluation tests, interviews, documentation, and observations Based on the results of learning scores from the pre-cycle, the first cycle is the first meeting obtained an average of 60.5 percentage of 25 percent including unfeasible criteria, the first cycle of the second meeting obtained an average of 70.5 percentage of 55 percent including eligible criteria, and the second cycle of the first meeting obtained an average of 70.5 percentage of 55 percent including eligible criteria. The results of this study based on the results of learning scores from pre-cycle obtained an average of 59.5 percentage of 15% including very unfeasible criteria, the first cycle is the first meeting obtained an average of 60.5 percentage of 25% including unfeasible criteria, the first cycle of the second meeting obtained an average of 70.5 percentage of 55 percent including eligible criteria, and the second cycle of the first meeting obtained an average of Keywords: Learning Outcomes, Flashcard, Thematic Learning